2023
DOI: 10.1186/s12891-023-06220-4
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent quasi-experimental ergonomic interventional study: long-term parallel four-groups interventions

Abstract: Background Musculoskeletal disorders (MSDs) are known as one of the main problems affecting the health of industrial workers and can lead to lost working days, functional disability of workers and wasting the financial resources of an organization. Therefore, the present study aimed to evaluating the effect of ergonomic interventions on reducing MSDs and improving working posture in the in a foundry industry workers. Methods A field multicomponent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, several scholarly articles have underscored the importance of periodic follow-up assessments to ensure their efficiency and sustainability (Esmaeili et al, 2023;Heidarimoghadam et al, 2020;Lin et al, 2022;Ramdan & Candra, 2021;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021). In terms of sample size or participant selection, certain articles employed mathematical formula to ascertain sample size (Dhole et al, 2021;Heidarimoghadam et al, 2020;Hijam et al, 2020;Lin et al, 2022;Mohammad Yusof et al, 2021;Rostami et al, 2022;So et al, 2019) while others either utilized the inclusion and exclusion criteria (Alghadir et al, 2021;Alipour et al, 2021;Antwi-Afari et al, 2021;Esmaeili et al, 2023;Kee, 2022;Kong et al, 2023;Motamedzadeh et al, 2021;Rahman et al, 2019;Ramdan & Candra, 2021;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021) or did not explicitly specify their sampling approach (Anshasi et al, 2022;Arunkumar et al, 2019;Darliana et al, 2020). Further analysis of the years of publication showed that a total of nine articles were published in 2021, which was the highest between 2018 to 2023.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations